Effect of xantham gum, steviosides, clove, and cinnamon essential oils on the sensory and microbiological quality of a low sugar tomato jam - Gliemmo, María Fernanda; Montagnani, Maria Andrea; Schelegueda, Laura Inés; Gonzalez, Malena Mariana; Campos, Carmen Adriana (2017)
The partial or total decrease of sugar content in the formulation of jams affects their physical, chemical and microbiological stability. In order to minimize these technological problems, we studied the effect of xanthan gum (XG), steviosides, cinnamon (CO), and clove (CLO) essential oils on the sensory and microbiological quality of a low sugar tomato jam. Levels of 0.250 g/100 g steviosides and 0.450 g/100 g XG showed maximum score of overall acceptability of jam. The combination of essential oils produced synergistic and additive effects in vitro on growth of Z. bailii and Z. rouxii, respectively. However, in the jam, CO was more effective and CLO did not modify the CO action. Cell surface was one of the sites of action of CO since a decrease in yeast cell surface hydrophobicity was observed. From the microbiological and sensory points of view, 0.0060 g/100 g CO showed the maximum score of jam overall acceptability and did not cause yeast inactivation but it could be useful as an additional stress factor against yeast post – process contamination. The adequate levels of XG, steviosides, and CO can improve the quality of a low sugar jam formulation.